Effect of the cPKCγ-Ng Signaling System on Rapid Eye Movement Sleep Deprivation-Induced Learning and Memory Impairment in Rats - Xu, Shu; Zhang, Yanbo; Xu, Zhiqing; Song, Luping (Frontiers in Psychiatry, 2021)
Objective: Rapid eye movement sleep deprivation (REM-SD) can cause a decline in learning and memory and lead to changes in behavior. Therefore, REM sleep plays a key role in processes that govern learning and memory. However, the mechanism underlying REM-SD-induced learning and memory impairment is unclear and the underlying molecular signaling still needs to be identified. In the present study, we investigated the role of the cPKCγ-Ng signaling pathway in REM-SD-induced learning and memory impairment. Method: Sixty male rats were divided into Control, REM-SD, REM-SD+cPKCγ activator PMA, REM-SD+cPKCγ inhibitor H-7, and sleep revival (SR) groups. The Morris water maze was used to assess spatial learning and memory. Western blot analysis was used to detect cPKCγ total protein expression and membrane translocation levels, and Ng total protein expression and phosphorylation levels. Results: The REM-SD group performed worse on the Morris water maze test than the control group. Western blot analysis showed that cPKCγ membrane translocation and Ng phosphorylation levels were significantly lower in the REM-SD group. SR following REM-SD restored learning and memory ability, cPKCγ transmembrane translocation, and Ng phosphorylation levels, but not to levels observed before REM-SD. PMA and H-7 significantly improved/disrupted task ability as well as cPKCγ transmembrane translocation and Ng phosphorylation levels in REM-SD rats. Conclusion: The REM-SD induced learning and memory impairment in rats and may be associated with the cPKCγ-Ng signaling pathway. Specifically, activation of the cPKCγ-Ng signaling pathway may protect against REM-SD.